ANALISIS KESIAPAN PENERAPAN STANDAR AKUNTANSI KEUANGAN ENTITAS PRIVAT (SAK EP) PADA KOPERASI SIMPAN PINJAM CREDIT UNION (CU) SUMBER KASIH SEJAHTERA - Desi Anggunsari; Hairul Anam; Butet Wulan Trifina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the readiness of the CU Sumber Kasih Sejahtera Credit Union (KSP) to implement Financial Accounting Standards for Private Entities (SAK EP). Using a qualitative method with a case study approach, data were collected through observation, interviews, and document analysis. The results of the study indicate that the cooperative’s readiness is supported by the implementation of the Fotress Digital Services (FDS) digital record-keeping system. The components of the financial statements are generated by the system in a complete and standardized manner. The implementation of the system and organizational support ensure that the application of the standards runs optimally. KSP CU Sumber Kasih Sejahtera is able to present relevant and reliable financial statements as a basis for decision-making, even though the board members’ conceptual understanding of the Financial Accounting Standards for Private Entities (SAK EP) remains limited.